(Gesichts)züge, Notation and Graphicness of Signs. Deconstruction in Wittgenstein’s Tractatus - Piekarski, Michał (Studia Philosophiae Christianae, 2022)
In this paper, I attempt to address some of the themes of Ludwig Wittgenstein’s Tractatus logico-philosophicus with the aim of their deconstructionist interpretation. My analysis is based on David Gunkel’s book Deconstruction (MIT Press 2021). Based on some of its findings, I show how the Tractatus allows deconstruction and its practice to be thought. I show that the graphic structure of signs is crucial for the young Wittgenstein’s analysis and that it justifies the metaphysical findings in favor of which he argues. ------------------------- Received:11/09/2022. Reviewed: 17/11/2022. Accepted: 1/12/2022.